Syntactic Function of That-Clause as Noun Clause in "Stories for Rainy Days" Novel - Annur Karima Zulyanputri; Sutiono Mahdi (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2020)
This research is concerned about the identification of that-clause as a noun clause in a novel entitled “Stories for Rainy Days”. This research aims to identify the syntactic function of that-clause and to identify the syntactic category of words or phrases that consisted of that-clause form. The analyzed data presented in this research is limited to 5 data. In regards to identifying the syntactic function of that-clause, the research utilizes the theory from Quirk (2010) and Klammer (2000). To analyze the syntactic category of words or phrases consist of that-clause form, this research implements theory from Alwasilah (1993). For the method of the research, this research applies qualitative descriptive method. Additionally, the finding of this research shows that that-clause can act as a subject, direct object, subject complement, adjective complement, and appositive. Continuously, this research shows that the form of that-clause must consist of a subject and a verb.